1995
DOI: 10.1111/j.1365-2303.1995.tb00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic analysis of breast aspirates

Abstract: Scanning electron microscopic analysis (SEM) of 50 pre-selected breast aspirates was performed after light microscopy and cytomorphological evaluation. SEM analysis of these aspirates revealed the presence of microvilli (mv), microprojections, blebs and irregular contours in malignant cells. Benign cells were regular, globular and smooth. SEM provided additional morphologic data which if used in conjunction with light microscopy can assist in reaching a correct diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 3 publications
0
19
0
1
Order By: Relevance
“…In accordance with studies on other CAPs, the specificity of LTX-315 for tumor cells is probably due to differences in cell membrane composition between cancer cells and non-malignant cells. Cancer cells have been shown to have a larger quantity of anionic molecules on their membrane [13, 14, 16], in addition to an increased membrane fluidity [17, 18] and membrane cell surface due to more microvilli [19, 20]. The cytotoxicity of LTX-315 was somewhat similar toward human melanoma cells (A375) and normal human primary melanocytes (PCS-200-013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with studies on other CAPs, the specificity of LTX-315 for tumor cells is probably due to differences in cell membrane composition between cancer cells and non-malignant cells. Cancer cells have been shown to have a larger quantity of anionic molecules on their membrane [13, 14, 16], in addition to an increased membrane fluidity [17, 18] and membrane cell surface due to more microvilli [19, 20]. The cytotoxicity of LTX-315 was somewhat similar toward human melanoma cells (A375) and normal human primary melanocytes (PCS-200-013).…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors that may contribute to the selective killing of cancer cells by ACPs include membrane fluidity and cell surface area. Compared to non-malignant cells, cancer cells often have a greater membrane fluidity [17, 18] and cell surface area (additional microvilli) [19, 20], hence leading to an improved anticancer activity of ACPs due to an increased membrane destabilization and the ability to bind more ACP molecules. Moreover, ACPs kill both drug-sensitive and drug-resistant cancer cells due to their membranolytic mode of action, independently of proliferative status and resistance phenotype [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…The microvilli are also more irregular in size and shape, which may be due to changes in structural proteins. 29 Defensins are also found to be effective against tumor cells by inducing tumor cell lysis, so the replacement of certain amino acids from L to D isomers in the peptide chain or modifying the peptide terminal (for example, amidation) will solve the problem and increase the compound's tumoricidal activity. 31 Putting the gene coding for the ribosomally synthesized antimicrobial peptide into the tumor cell can avoid this type of loss in activity.…”
Section: Properties Of Ribosomally Synthesized Antimicrobial Peptidesmentioning
confidence: 98%
“…The basic difference between the cell membranes of malignant cells and normal cells accounts for the ability of certain antimicrobial peptides to show cytotoxic effects against the cancer cells (anticancer peptides) without causing any harm to the healthy cells. 29 Antimicrobial peptides have the capacity to interact with the negatively charged molecules that are present in the target, but tumor cells are different in their membrane composition. 30 The membrane fluidity of cancer cells is greater than that of untransformed cells, which may enhance the lytic activity of anticancer peptides by facilitating membrane destabilization.…”
Section: Properties Of Ribosomally Synthesized Antimicrobial Peptidesmentioning
confidence: 99%
“…Cholesterol content on tumor cells' membrane also modulates cellular fluidity and condition ACPs activity (Schweizer 2009). The higher transmembrane potential and the higher surface area of tumor cells, which promotes contact with an increased number or peptide molecules, further contribute to the preferred action of ACPs on tumor cells (Chan et al 1998;Chaudhary and Munshi 1995;Huang et al 2014). Peptides such as MPI-1 from the venom wasp Polybia paulista (Wang et al 2009a), NK-2 derived from the protein NK-lysin found in porcines' NK-an T-cells (Schroder-Borm et al 2005) and the synthetic peptide SVS-1 Sinthuvanich et al 2012) are a few examples of natural and synthetic peptides that base their preference for solid and hematological tumor cells based on the membrane surface net charge.…”
Section: Mechanisms Of Action Cellular Targets and Selectivity Of Anmentioning
confidence: 99%